(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This scientific article analyzes the methods of developing students’ creative thinking in the process of teaching fine arts based on modern pedagogical, psychological and art history approaches; the essence of creative thinking, its role in fine arts education, its inextricable connection with artistic thinking and imagination are scientifically and theoretically substantiated; the article broadly covers the didactic possibilities of problem-based learning, free creativity, associative thinking, variant artistic solutions, collective creativity, analysis and reflection, as well as methods based on modern digital technologies; the results of the study show that organizing fine arts classes based on innovative approaches significantly increases students’ creative activity, aesthetic taste and independent artistic decision-making skills.